2001
DOI: 10.4269/ajtmh.2001.65.777
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of Australian brushtail possums, Trichosurus vulpecula (Phalangeridae: Marsupialia), with Ross River and Barmah Forest viruses by use of a natural mosquito vector system.

Abstract: Abstract. Brushtail possums, Trichosurus vulpecula Kerr, were experimentally infected with Ross River (RR) or Barmah Forest (BF) virus by Aedes vigilax (Skuse) mosquitoes. Eight of 10 animals exposed to RR virus developed neutralizing antibody, and 3 possums developed high viremia for Ͻ 48 hr after infection, sufficient to infect recipient mosquitoes. Two of 10 animals exposed to BF virus developed neutralizing antibody. Both infected possums maintained detectable neutralizing antibody to BF for at least 45 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Native animals such as kangaroos and wallabies are thought to be the major vertebrate hosts of BFv, but other species may also play a role (Mackenzie et al 1994;Russell, 1998). Recent evidence suggests that brushtail possums, dogs and cats can be infected by BFv but they are unlikely to be important hosts in the natural transmission cycles (Boyd et al 2001;. Queensland is the fastest-growing state in Australia, and there have been many socio-ecological changes (e.g., population growth, urbanization, and land clearing) occurring over the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Native animals such as kangaroos and wallabies are thought to be the major vertebrate hosts of BFv, but other species may also play a role (Mackenzie et al 1994;Russell, 1998). Recent evidence suggests that brushtail possums, dogs and cats can be infected by BFv but they are unlikely to be important hosts in the natural transmission cycles (Boyd et al 2001;. Queensland is the fastest-growing state in Australia, and there have been many socio-ecological changes (e.g., population growth, urbanization, and land clearing) occurring over the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…These data support the possibility of marsupials serving as amplifying hosts for RRV in urban areas in Australia. Consideration also needs to be given to the possibility that other potential hosts, such as horses and the common brushtail possum (Trichosurus vulpecular), contribute to virus maintenance and transmission (Pascoe et al 1978, Kay et al 1987, Boyd et al 2001. A more recent serosurvey in New South Wales indicated that common brushtail possum populations from urban and woodland habitats were negative for the presence of RRV antibodies (Hill et al 2008).…”
Section: Potter Et Almentioning
confidence: 99%
“…Watson and Kay (1998) have highlighted the vector competence of A. notoscriptus mosquitoes for RR virus in urban areas, while Dale and Morris (1996) have focused on the development of a rapid predictor of potential breeding areas for C. annulirostris mosquitoes in urban areas. Research has also shown that brushtail possums (Trichosurus vulpecular) (Boyd et al, 2001), and captive tammar wallabies (Macropus eugenii) and wallaroos (Macropus robustus) (Old and Deane, 2005) have potential to act as reservoir hosts of RR virus in urban areas. The temperature and rainfall levels in tropical and subtropical regions allow adult vectors to remain active all year (Kay and Aaskov, 1989;McMichael et al, 2003) and given low immunity in host populations, virus amplification occurs, extending to human populations (McMichael et al, 2003).…”
Section: Ross River Virus Disease and Concernsmentioning
confidence: 98%